RIVER MORPHOLOGICAL STUDY OF DOWNSTREAM PANEKI RIVER IN PALU WATERSHED FOLLOWING THE EARTHQUAKE AND LIQUEFACTION DISASTER AT CENTRAL SULAWESI - Albert Kaunang, James
Earthquake struck Central Sulawesi Province in 2018 triggered liquefaction in several locations, such as Jono Oge village located at Sigi Regency, Central Sulawesi Province, where the middle stream of Paneki River flows. Liquefaction caused the Paneki River wash in the densely populated settlement became narrower and shallower due to “flowing” material. In response to the damage Ministry of Public Works and Housing (MPWH) through River Basin Management of Sulawesi III initiates project River Improvement and Sediment Control in Paneki River. The implementation of this project will surely affect the river behaviour, especially on morphological aspects, therefore this study presents a study of the Paneki River discharge capacity and morphological analysis due to river improvement and sediment control projects. This study covers, flood and bankfull discharge calculation of the river utilizing the Unit Hydrograph method, rainfall data, and river discharge measurement. River geometry and shop drawing data are used to set up a numerical model. Continuity Equation and momentum Equation solved numerically through Implicit Finite Volume Scheme are used for the hydraulic analysis of the model, in addition, river bed material data introduced into the model to simulate sediment transport of the river. Changes in the river morphology in form of river bed aggradation and degradation will be included as a results of sediment transport simulation which are verified and examined using field data and conditions. Model simulation result shows that the maximum discharge capacity of Paneki river is 259.81m3/s, bed in upstream and downstream area of Paneki River degrade, with consolidation dam (CD-1) stabilized the river bed upstream of the dam to 2740 m relative to the river outlet. Stabilization due to the position of CD - 2 could be described using the following equation of ????= ?1018ln(????)+7208.1, furthermore the average degradation of the downstream area could be described with ????=0.017????0.6701.